Partisipasi Masyarakat dalam Penyusunan Rencana Pembangunan Jangka Menengah Desa (RPJMDES) di Desa Tembung Kecamatan Percut Sei Tuan Kabupaten Deli Serdang. - Adelina M Aritonang; Ertika Susanti Pasaribu; Pebryna Riosa Siburian; Julia Ivanna (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Village development is an important pillar in national development, where community participation is a key factor in achieving success. The Village Medium-Term Development Plan (RPJMDes) serves as a strategic document that guides development policies and programs at the village level, with community involvement crucial to ensure that their needs and expectations are met. This study identified three important aspects of community participation: as a tool to obtain information, to increase trust in development programs, and as a democratic right. Despite challenges in involving the community, such as a lack of understanding of planning mechanisms and time constraints, the hope for increasing participation remains. Qualitative research methods were used to explore the most effective methods in increasing community involvement. The results showed that active community participation in the preparation of the RPJMDes in Tembung Village can increase transparency, accountability, and relevance of development programs, thus creating inclusive and sustainable development. Cooperation between residents and the village government is the key to achieving optimal development results that are felt by all levels of society.